Optimizing video compression using robust parameter design - Wojciechowski, E.; Phadke, M.S. (2001 IEEE Global Telecommunications Conference - Globecom, 2001)
Modern military communications systems require the transmission of full motion video over a hostile battlefield environment. In order to operate over a limited channel bandwidth, the video information must be compressed several orders of magnitude. Recent advances in Internet telephony and high definition television (HDTV) have made real time video compression a reality. The H.263 video compression standard investigated by this project, takes advantage of image redundancies in both space and time. However, this standard was designed for a benign commercial environment. Using it effectively in a military environment requires additional parameter optimization. Through a series of L/sub 86/ parameter design experiments, a strategy was developed which identified the H.263 video codec parameters that had the greatest impact on both video quality and transmitted bitrate. Using Taguchi experiment techniques, an optimal arrangement of control parameters was developed and tested.